41.6k views
2 votes
Solve the following equation: 3x + 6 = 9​

User Anil M H
by
4.8k points

2 Answers

7 votes

Answer:

x=1

Explanation:

Subtract 6 from both sides of the equation, leaving 3x=3.

We put both sides over 3 to divide.

We are left with x=3

To test this, we substitute x with 1.

3(1)+6=9

3+6=9

9=9

User Emporerblk
by
4.3k points
1 vote

Answer:

Explanation:

3x+6=9

3x=9-6

3x=2

x=1.5

User Jeremy Matt
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.